The passion factor - Leal, Silvia; Filgueira, Jorge (LID Editorial, 2017)
This book provides an effective methodology and an essential tool so that entrepreneurs, managers and business leaders can nurture innovative behaviour in the workplace by effectively managing its three essential dimensions: people, the business organisation and motivation. It then goes on to show how the three factors, Insight (for understanding and appreciating new ideas), Sex (the differential factor between men and women when it comes to innovation) and Passion (the ambition and courage needed to create new strategies) all play a role on the path to innovation.